Theology without Walls: The Transreligious Imperative, edited by Jerry L. Martin. - Gustafson, Hans S (Interreligious Studies and Intercultural Theology, 2022)
Theology without Walls: The Transreligious Imperative, edited by Jerry L. Martin. Routledge, 2020. xviii + 250 pp., Pb., 48.95 US. ISBN: 978 1032088631.